Revealing the existence of long-range liquid-liquid interfacial potential in phase-transfer processes - Ow, Matthew Jun Kit (2024)
By employing fluorescence wide-field microscopy and a nanoparticle-based phase transfer catalyst (PTC), consisting of a fluorescent silica nanoparticle functionalized with trioctylpropylammonium bromide, we demonstrate that in the presence of NaOH, single nanoparticles display subdiffusive motion along the axis normal to an aqueous liquid-organic liquid interface. This is because of an extended interfacial potential with a shallow well (∼1 kBT) that stretches a few μm into the organic phase, in contrast to previous molecular dynamics studies that reported narrow interfaces on the order of ∼1 nm. Spontaneous interfacial emulsification induced by NaOH results in the propagation of water-in-oil nanoemulsions into the organic solvent that creates an equilibrium hybrid-solvent composition that solvates the PTC. A greater mobility and longer residence time of the PTC at the potential well enhance the interfacial phase transfer process and catalytic efficiency.